An Update on Molecular Diagnostic Testing of Human Imprinting Disorders - Grafodatskaya, Daria; Choufani, Sanaa; Basran, Raveen; Weksberg, Rosanna (Journal of Pediatric Genetics, 2017)
Imprinted genes are expressed in a parent of origin manner. Dysregulation of imprinted genes expression causes various disorders associated with abnormalities of growth, neurodevelopment, and metabolism. Molecular mechanisms leading to imprinting disorders and strategies for their diagnosis are discussed in this review article.
Keywords: genomic imprinting; epigenetics; DNA methylation